The shipyard agent : Augusta Clawson and the women welders of World War II - Hodgins, Beverly Lionberger, 1950- (Lyons Press, 2025)
"The Shipyard Agent reveals the untold story of Augusta Clawson, the undercover investigator who helped shape the future for World War II's women welders.From the Pacific Northwest to the Gulf Coast and up the Eastern seaboard, during World War II women welders worked at a fever pitch in the nation's shipyards to assemble the behemoths that would safely carry their men to war. Some dubbed these women "Wendy the Welder" or referred to them as "welderettes," as though the work they did was an imitation or substitution for that done by the male welders. But there was nothing dainty or feminine about the exact, difficult, and exhausting work that female welders performed.In 1943, Special Agent Augusta Clawson of the U.S. Office of Education was assigned to work with industries and employment agencies preparing and training women for jobs in war-production factories. Her special agent position became clandestine when she was sent to the shipyard on Swan Island in Portland, Oregon, with an extraordinary assignment. Without identifying the true nature of her role, she was to present herself as one of the many women traveling to work in the shipyards, so that she could observe an unfiltered representation of the world of women welders. Her goal was to learn why some women-especially the welders-were quitting after only a short time on the job.Clawson entered Swan Island Shipyard exactly as many other women did, inexperienced and untrained, and soon joined the ranks of female welders. Meanwhile she surreptitiously sent reports back to Washington, DC, cataloging her daily observations and experiences. Her frank and honest reports-the truth as only a woman welder could tell it-were published in 1944 under the title Shipyard Diary of a Woman Welder, but the full story of her instrumental role in establishing improved training and safety guidelines for the women laboring to build America's ships has not been told-until now"-- Provided by publisher.